2007
DOI: 10.1002/esp.1544
|View full text |Cite
|
Sign up to set email alerts
|

Field investigation on rilling in the experimental Sparacia area, South Italy

Abstract: In this paper the results of a field investigation on rilling carried out in the experimental Sparacia area are reported.The measurements were made on a plot 6 m wide and 22 m long subjected to natural rainfalls. For ten rainfalls the total soil loss (interrill and rill erosion) was collected in a storage system consisting of two tanks arranged in series at the base of the plot. Rill morphology (rill length and cross-sections) was measured for five rainfall events, while the rill profile was surveyed for three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
96
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 27 publications
3
96
0
3
Order By: Relevance
“…Therefore these indicators of rill formation could be used to predict the rill erosion amount and total erosion amount on slope land. This conclusion coincides with observations made by Capra et al (2005) and Bruno et al (2008). Capra et al (2005) showed that the total rill length is the best estimator of the erosion volume by comparing different topographic indices.…”
Section: Correlations Among the Indicators Of Rill Erosionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore these indicators of rill formation could be used to predict the rill erosion amount and total erosion amount on slope land. This conclusion coincides with observations made by Capra et al (2005) and Bruno et al (2008). Capra et al (2005) showed that the total rill length is the best estimator of the erosion volume by comparing different topographic indices.…”
Section: Correlations Among the Indicators Of Rill Erosionsupporting
confidence: 91%
“…Capra et al (2005) showed that the total rill length is the best estimator of the erosion volume by comparing different topographic indices. Bruno et al (2008) also pointed out that rill length was useful for estimating the severity of rilling in a given region. At the same time, there were also good correlations among other indicators of rill formation.…”
Section: Correlations Among the Indicators Of Rill Erosionmentioning
confidence: 99%
“…(4) was tested by Caraballo-Arias et al (2014) for the 25 badland channels. Figure 3 shows the relationship (4) calibrated by L-V pairs observed on rills, EGs and gullies by Ichim et al (1990), Daba et al (2003), Bruno et al (2008), Moges and Holden (2008) and Di Stefano and Ferro (2011). This figure demonstrates that the power equation (4) can be applied for rill, EG and gully data using the same exponent b, equal to 1.1, and a different scale factor (a = 0.0036 for rills, a = 0.0984 for EGs and a = 35.8 for gullies).…”
Section: Badland Morphologymentioning
confidence: 98%
“…Durante los eventos extremos, se produce la concentración del flujo superficial, dando lugar al desarrollo de surcos y a elevadas tasas de erosión (Bruno, Di Stefano & Ferro, 2008). La formación de los surcos y su desarrollo incrementa el transporte de sedimentos.…”
Section: Introductionunclassified
“…La formación de los surcos y su desarrollo incrementa el transporte de sedimentos. Así, se ha demostrado, en diversos ensayos de campo, cómo para aquellos eventos erosivos en los cuales se genera erosión por surcos, la contribución de esta a la pérdida total de suelo es dominante (Bruno et al, 2008;Rejman & Brodowski, 2005).…”
Section: Introductionunclassified